(untitled) (Medico Legal Update, 2021)
The proposal target was determining the gene expression and single nucleotide polymorphism of Androgen receptor gene (rs6152 G>T) in blood sample of recurrent spontaneous abortion (RSA) Iraqi females. Fifty females (n=50) with RSA consulted Al-Elwiya teaching hospital from February to June 2019 and apparently healthy fertile control (n=50) were enrolled. DNA and RNA were extracted from leucocytes to detriment the SNP and gene expression which were carried out by (RT-q PCR). The results showed non -significant difference (p>0.05) in the mean of threshold cycle(?Ct) of androgen receptor gene between female with RSA and control. Assessing the 2???Ct in female with RSA, non -significant decreased expression of folding in androgen receptor m RNA compared with control. The genotypes and allele frequencies in the two groups showed significant decrease in the heterozygous (GA) and mutant (AA) genotype frequencies in female with RSA, the frequency of wild (GG) genotype is increased in female with RSA. In conclusion, expression of androgen receptor gene didn’t affect in female with RSA, the mutant genotype may play as protective SNP against RSA.